2017
DOI: 10.4172/2329-6836.1000262
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Activity of Some Tamaricaceae Plants

Abstract: The antipyretic activity of the alcoholic extracts for the Tamarix aucheriana, T. nilotica, and T. aphylla were measured in the Wistar albino male rats (150-180 g) by using a yeast-induced hyperpyrexia test. The carrageenaninduced paw edema method. The anti-inflammatory activity of the T. aucheriana, T. nilotica, and T. aphylla extracts was measured. The edema was expressed as an increase in paw volume. The analgesic activity of the alcoholic extracts of the T. aucheriana, T. nilotica, and T. aphylla were impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Therefore, it can be concluded that the dose of 4000 mg/kg was well-tolerated and did not produce any toxicological changes in the physical condition and appearance of the rats. These findings are consistent with previous studies, which reported that LD50 of TA is above 1500 mg/kg BW, and revealed that the methanolic extract of TA produced no toxic symptoms in graded doses up to 4000 mg/kg in acute and sub-chronic toxicity studies [ 28 , 29 ]. Based on OECD guidelines for testing chemicals, the methanolic extract of TA was considered safe [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it can be concluded that the dose of 4000 mg/kg was well-tolerated and did not produce any toxicological changes in the physical condition and appearance of the rats. These findings are consistent with previous studies, which reported that LD50 of TA is above 1500 mg/kg BW, and revealed that the methanolic extract of TA produced no toxic symptoms in graded doses up to 4000 mg/kg in acute and sub-chronic toxicity studies [ 28 , 29 ]. Based on OECD guidelines for testing chemicals, the methanolic extract of TA was considered safe [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Yusufoglu and Alqasoumi (2011), who evaluated the wound healing activity of T. aphylla extract using the excision wound model to monitor wound contraction and wound closure time, reported that the plant extract accelerated the wound healing process by reducing wound contraction and wound half closure time. The use of the bark of T. aphylla to treat hepatitis, an inflammation of the liver caused by viruses, was also reported previously (Akhlaq & Mohammed, 2011;Nawwar et al, 2009) but was not confirmed in in vivo studies; hence, the plant extract has shown antioxidant activity (Mahfoudhi, Ben Salem, et al, 2016;Qadir et al, 2014) and a significant anti-inflammatory effect when tested in Wister albino rats using a carrageenaninduced paw edema test (Al-Jaber & Allehaib, 2017;Iqbal et al, 2017). A significant proportion of the respondents reported the use of T. aphylla leaves to relieve joint pain, headache, and rheumatism.…”
Section: Literature-based Proof Of Biological and Pharmacological Activitiesmentioning
confidence: 73%
“…Antioxidant, analgesic and antipyretic activities (Al-Jaber & Allehaib, 2017;Mahfoudhi, Ben Salem, et al, 2016;Qadir, Abbas, Hamayun, & Ali, 2014). Antidiabetic (Mahfoudhi, Grosso, et al, 2016).…”
Section: Rootmentioning
confidence: 99%
“…Literature dealing with antiproliferative effect of t. gallica is relatively poor. Nevertheless, many studies reported anti-inflammatory, analgesic antioxidant, antihyperlipidemic, antiviral, cytotoxic, anti-Alzheimer and Type 2 Diabetes Diseases activities [14][15][16][17][18][19][20]…”
Section: C6 Cellsmentioning
confidence: 99%